2009
DOI: 10.1111/j.1365-2567.2009.03102.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesangial cell complement receptor 1‐related protein y limits complement‐dependent neutrophil accumulation in immune complex glomerulonephritis

Abstract: SummaryThe absence of complement receptor 1 (CR1) related gene/protein y (Crry) leads to embryonic lethality as a result of unrestricted complement activation and concomitant neutrophil infiltration. Here we used Crry )/) C3 +/) mice to investigate the role of Crry in the pathogenesis of immune complex glomerulonephritis (GN). After 3 weeks of immunization with horse spleen apoferritin, six of nine Crry )/) C3 +/) mice and none of the six control C3 +/) mice developed proliferative GN (P = 0Á010). After 5 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…54 Serum C3 levels, anti-dsDNA antibodies, and circulating IC levels were determined by ELISA as described previously. 11,12,67 Serum samples obtained from the survival study from 6 to 16 weeks were included.…”
Section: Measurements From Blood and Urinementioning
confidence: 99%
“…54 Serum C3 levels, anti-dsDNA antibodies, and circulating IC levels were determined by ELISA as described previously. 11,12,67 Serum samples obtained from the survival study from 6 to 16 weeks were included.…”
Section: Measurements From Blood and Urinementioning
confidence: 99%
“…Crry −/− C3 +/− mice actively immunized with horse spleen apoferritin had increased development of GN relative to controls, which could be attributed to neutrophil infiltration; absent staining for alpha-smooth muscle actin and proliferating cell nuclear antigen suggested that mesangial cell proliferation did not play a significant role in this model. 78 In comparable studies to examine potential roles for DAF and CD59, both DAF −/− and DAF −/− CD59 −/− mice had significantly increased glomerular C3 deposition which correlated with development of GN relative to wildtype controls. 79 There were no histological or functional disease features in CD59 −/− or wildtype mice with CSS, which is indirect evidence that C5b-9 has a limited role in this model.…”
Section: Immune Complex-mediated Glomerulonephritismentioning
confidence: 98%